-3(6-5a)=9a+24

Simple and best practice solution for -3(6-5a)=9a+24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6-5a)=9a+24 equation:


Simplifying
-3(6 + -5a) = 9a + 24
(6 * -3 + -5a * -3) = 9a + 24
(-18 + 15a) = 9a + 24

Reorder the terms:
-18 + 15a = 24 + 9a

Solving
-18 + 15a = 24 + 9a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9a' to each side of the equation.
-18 + 15a + -9a = 24 + 9a + -9a

Combine like terms: 15a + -9a = 6a
-18 + 6a = 24 + 9a + -9a

Combine like terms: 9a + -9a = 0
-18 + 6a = 24 + 0
-18 + 6a = 24

Add '18' to each side of the equation.
-18 + 18 + 6a = 24 + 18

Combine like terms: -18 + 18 = 0
0 + 6a = 24 + 18
6a = 24 + 18

Combine like terms: 24 + 18 = 42
6a = 42

Divide each side by '6'.
a = 7

Simplifying
a = 7

See similar equations:

| factorx^2+6x-27=0 | | -2(4t-4)+5t=8t-5 | | y+2y-12=3 | | (w+6)(w-1)+(12w+7)(w-1)=0 | | -.75z+.8z=0.05 | | 7k-14-2k=21 | | 500+22x=1204 | | 3x+7+x+30+1=70 | | 4t-9=1-t | | 12x-4=12(x-7) | | 4d+2-2=6+3d | | y-4x-3=0 | | 5x-20=25-4x | | 5(3x+2)=2(2x-6) | | -6y-2y=-12 | | 3z+12=2z+5 | | 5t-9=2t+3 | | 4-6n=32 | | 2x+24=30+x | | 2x+24=30+c | | -7x+4+3x=12 | | 0.25r-0.25=0.5-0.25r | | 10+3x=-5x+26 | | 2n^2+n-28=0 | | 3x-(10+4x)=-3x-8 | | x^2+5x+4+x^3=0 | | 1.15y+1.25y=15 | | 2+2x=a | | -33+10x=x+2x+100 | | 13=5-2y | | 2544c-0967b+-123c=x | | -6(5-2x)=17 |

Equations solver categories